Effect of land-use on soil water dynamic in dehesas of Central–Western Spain - Cubera, Elena; Moreno, Gerardo (Catena, 2007)
Dehesa ecosystems are open woodlands with scattered oak trees as their main component. As a result of differing land-uses, the structure of vegetation found within dehesas varies between: (i) oak trees and intercropped cereals (cropped), (ii) oak trees and native grass vegetation (grazed), and (iii) oak trees with abundant understorey shrubs (encroached). The aim of this study is to investigate whether land-use influences the water dynamics of dehesas by measuring available soil water content (AWC) in the upper 250 cm of the soil at different distances from tree trunks (maximum 30 m) at four Quercus ilex dehesas in Central–Western Spain. The technique used was Time Domain Reflectometry and the study was undertaken between May of 2002 and December of 2005. Leaf water potential (Ψ) was also measured on trees at one site by mean of a pressure chamber. Within the upper meter of the soil, it appears that trees, grasses and shrubs extracted soil water resources in a similar way from both beneath and beyond the tree canopy. However, encroached plots in general showed lower average AWC values than cropped or grazed plots (3.7, 5.6, and 6.2% in encroached, cropped and grazed, respectively). Cereal crops do not compete more strongly than grasses with trees for available soil water resources. The similar Ψ values found at cropped and grazed plots supported these results. From our results, it could be hypothesized that ploughed dehesas could facilitate soil re-watering in the plots with pronounced slopes. The decrease of AWC values at encroached plots with respect to the cropped and grazed plots was found mostly beyond the tree trunk at deeper soil layers, indicating that shrubs use water partly not accessible to trees. The presence of an understory of shrubs seems to have slightly increased the water constraints on trees during the summer period (Ψd values of −0.5, −0.5, and −0.8 MPa in cropped, grazed, and encroached plots, respectively). In cropped and grazed plots, an important amount of water seems to have remained unused for trees and grasses.
Keywords: available water content; cultivation; Encroachment; fertilisation; Land-use